"A noite branca", between the Documentary and Fictional: the Silenced Account of the Blue Division - Vilavedra, Dolores (Madrygal. Revista de Estudios Gallegos, 2015)
The article explores the ambiguous phenomenological status of the novel A noite branca (The White Night) by Francisco Fernández Naval, published in Galician in 2012. This ambiguity is produced by the discursive hybridity of the novel and by the vague ontological status of facts narrated and by several characters. The clarification of the strategies of the said ambiguity, and the originality of the subject, in the whole of Galician narrative about the memory of Civil War and Postwar can tightly evaluate the literary merits of the novel.
Keywords: Memory; Civil War; Galician Narrative; Epistolary Literature; Documentary Literature; Blue Division.